Optimization of a Composite Wing Subject to Multi Constraints - Fu, Qiang (Cranfield University, 2013)
In this thesis, an investigation has been carried out into a minimum weight optimization analysis of a composite wing with multi design constraints under both static and dynamic loadings. The study includes the influence of a morphing leading edge on the wing stiffness and gust load reduction by employing a passive gust alleviation device at the wing tip. The design process started from a generic study of optimal structure against buckling for three typical types of reinforced skin panel structures including stiffener panel, sandwich and grid panel. The optimal design in terms of buckling performance and structural efficiency were compared. The study then focused on the optimal design of stiffened skin panels for a particular wing. Parametric studies on optimal design for isotropic stiffened panels were carried out in which practical design constraints were introduced. The optimal design method was further extended to composite stiffened skin panels. Optimal designs were obtained within a compression distributed load range from 500 N/mm to 5250 N/mm and a symmetric balanced layup with 0˚, 90˚, and ±45˚ plies. Based on the study, the modelling and optimal design method for composite stiffened panels was applied to a composite wing box for its upper surface panel design. The initial composite wing box was designed to achieve a minimum weight. Gradient based optimization method was applied in the analysis with practical design constraints. The results indicate that the effect of leading edge morphing on the overall wing structural stiffness is negligible. It has been shown that the weight of the upper surface of the wing box structure can be reduced by 19.8% from its initial design. Optimal design of a passive gust alleviation device (PGAD) mounted at the wing tip was then investigated. Based on the dynamic analysis of the 3D wing FE model in different flight and payload cases, a method and program was developed to create a dynamically equivalent beam model. Gust response of the optimized wing model was computed for a wide range of frequencies in accordance with the CS-25. Next, a parametric study of the key design variables of the PGAD was carried out to determine the optimal design parameters for minimum gust loading. The results have shown that the gust response can be reduced by 15% by using a 1m long PGAD for a conventional aircraft wing and yet reduce 50% tip displacement with 37.2% bending moment at wing root for a flying wing concept aircraft wing with 1.6m long PGAD mounted at the wing tip. The results of the investigation contribute to knowledge in the following aspects. It provides an evaluation of the structural efficiency of three typical types of stiffened panels against buckling prevention. The research also provided an optimal design method for composite stringer stiffened panels by combining theoretical and practical design constraints. It made possible for the first-time a numerical evaluation of the novel PGAD as applied to a large aircraft.